PengembanganVariasi Desain Berbasis Artistic Computer Aided Manufacturing (ArtCam) dan Rapid Prototyping (RP) untuk Meningkatkan Daya Saing Souvenir - Bawono, Baju; Anggoro, P. Wisnu; Yuniarto, A. Tonny Yuniarto (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2015)
The purpose of this study was to improve product design variations artistic brass souvenirs through of technology Rapid Prototyping (RP) to create the master mold brass products so as to increase the competitiveness of the product in the eyes of consumers. Market research will be conducted to identify consumer buying interest and identify distinguishing excellence needed to build the concept of product development brass. The research results in the form of a distinctive design trades selected areas further using software designed Artistic Computer Aided Manufacturing (ArtCAM) and translated into a master mold by a 3D engine utilizing Object 30Pro RP technology. This research will be focused on optimizing the manufacturing process so that the brass souvenirs is expected to appear as a continuous improvement effort to improve the competitiveness of the industrial centers Ngawen souvenirs.